Final Report Part I - Alternative Federal Day Care Strategies for the 1970's. Summary Report. - Institute for Interdisciplinary Studies, Minneapolis, Minn.; Institute for Interdisciplinary Studies, Minneapolis, Minn. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
In view of the need for child care services throughout the country, some alternative Federal day care strategies for the decade are described. Major sections deal with existing child care systems, whether the Federal Government should provide more day care services, whether child development services should be provided in federally supported day care arrangements, an analysis of alternative Federal delivery system strategies for further involvement in the day care industry, and implementation of the recommendations. Emphasis on legislation guidelines, enactment, and impact. Supporting appendices are included on existing day care legislation, costs, challenges in day care expansion, public opinion toward day care, types of care and parents' references, future trends affecting day care and preschool education, and training programs for child care personnel. An annotated bibliography is also included. (LH)
Sponsoring Agency: Office of Economic Opportunity, Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Child Care; Day Care; Government Role; Legislation; Planning; Policy Formation